The Effect of Sago Sugar Substitution on the Organoleptic Quality ofSeaweed (Eucheuma cottonii) Jam - Juliansyah Juliansyah; Desmelati Desmelati; Dahlia Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThis study aimed to determine the effect of sago sugar substitution on the organoleptic quality of seaweed (Eucheuma cottonii) jam. The research method used was experimental with non-factorial completely randomized design (CRD) using the addition of sago sugar with different amounts consisting of G0 (0 g), G1 (100 g), G2 (200 g), G3 (300 g). Parameter analysis was an organoleptic test (taste, texture, color, aroma). The results of the organoleptic analysis showed that the seaweed jam with the addition of 300 g sago sugar had the highest value (taste, texture, color, and aroma) than the addition of 100 g sago sugar and 200 g sago sugar. The addition of sago sugar affected the quality of seaweed jam. Seaweed jam with the addition of 300 g sago sugar produced a jam with the characteristics of a sweet taste, thick texture, clean and shiny color, and a specific aroma of seaweed jam.Keywords: characteristics, organoletics, sagu sugar, seaweed jam